Safety of Vojta's reflex locomotion in term pregnancy: a randomized controlled pilot study of uterine activity and labor onset - Milan, Martinek; Jan, Zapletal; Vit, Drochytek; Nikola, Janovska; Barbora, Svedova; Anna, Babkova; Radovan, Vlk; Lukas, Rob; Michael, Halaska Jiri; Tereza, Novakova (Scientific reports, 2026)
The Vojta's method (VRL) is a neurophysiological rehabilitation method used to support and induce reflex responses of locomotor and vegetative systems. It uses involuntary motor reaction of the body during pressure stimulation of so-called trigger zones. Pregnancy is currently considered a contraindication for the use of VRL due to the potential risk of inducing regular uterine activity and, consequently, triggering labor. The aim of the study is to evaluate changes in uterine activity during Vojta's reflex locomotion and to determine whether the method is associated with the induction of labor. Secondary goal is to assess its safety in term pregnancy and its potential use for rehabilitative purposes. This single-center, single-blinded, parallel-group randomized controlled pilot trial included 40 pregnant patients between 40 + 0 to 41 + 0 weeks of gestational age. Participants were randomized (sealed envelope method) to receive either stimulation of trigger zones according to VRL (n = 20) or sham stimulation (n = 20). Cardiotocographic (CTG) recordings were conducted right before and immediately after stimulation and evaluated by two independent obstetricians. Additionally, participants completed a questionnaire evaluating subjective responses to stimulation. Primary outcomes were CTG-detected uterine changes and time from stimulation to delivery. Secondary outcomes included self-reported sensations and pain intensity (VAS). None of the patients delivered as a result of VRL stimulation. CTG showed increased uterine activity in 45% of VRL stimulated participants vs. 10% in the control group. Median time to labor onset in the VRL group was 5 days (1-8), compared to 4 days (1-9) in the control group. VRL was well tolerated (mean VAS 1.85), but rated significantly less pleasant than sham (p = 0.043). Our findings suggest that the use of VRL in term pregnancy is likely safe and well tolerated. While uterine activity was observed in 45% of cases, this activity was not sufficient to induce labor. Our findings, however, do not support pregnancy as a blanket contraindication.Trial registration: This clinical trial was registered at http://clinicaltrials.gov (ID: NCT06339528).
Keywords: Locomotion; dospělí; ženské pohlaví; lidé; Pregnancy; Single-Blind Method; lokomoce; Term pregnancy; pilotní projekty; Reflex; Cardiotocography; jednoduchá slepá metoda; kardiotokografie; Humans; nástup porodu; těhotenství; Neurorehabilitation; Adult; uterus; Pilot Projects; Uterus; Vojta’s therapy; reflex; Labor Onset; Female